Fever in children: How to minimise risk and provide appropriate therapy - Robin J. Green; Adéle Pentz (South African Family Practice)
The management of fever in children is a subject that garners many different opinions and interventions. Various approaches seem to be acceptable, from the physician who never uses antipyretic medication, to the use of multiple combination therapies. Following the recent publication of guidelines for the management of acute fever in children, there is now a standard against which fever in children should be managed. These guidelines aim to standardise the process of examining pyrexial children, elicit a reasonable history and then investigate the likely illnesses, so as to justify appropriate therapy.